The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/0104-530x1655-14
|View full text |Cite
|
Sign up to set email alerts
|

Análise de viabilidade técnica e econômica do uso de água de chuva em uma indústria metalmecânica na região metropolitana de Curitiba PR

Abstract: Resumo Este estudo tem por objetivo verificar a possibilidade de aproveitamento da água da chuva em uma indústria metalmecânica localizada no município de São José dos Pinhais, região metropolitana de Curitiba, considerando o volume de chuvas, necessidade da indústria, as características de qualidade da água de chuva da região, além de uma simulação da cobrança pelo uso da água e emissão dos seus efluentes lançados em um córrego próximo. Nesta avaliação, verificou-se que o aproveitamento da água de chuva pode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…The area destined to the cistern implementation, despite having a lower percentage (18.20%) compared to the group improvements, should be considered because it could be for another productive activity. Comparisons regarding values and percentages for the implementation of the infrastructure to collect rainwater were not possible because of the lack of details of investments in the few studies found in the literature (M. Santos, Carvalho, Ramos, Dias, & Reis, 2016;Teixeira et al, 2016). Also, some of these studies lack information such as investment in catchment gutters and/or the area where the cistern is located .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The area destined to the cistern implementation, despite having a lower percentage (18.20%) compared to the group improvements, should be considered because it could be for another productive activity. Comparisons regarding values and percentages for the implementation of the infrastructure to collect rainwater were not possible because of the lack of details of investments in the few studies found in the literature (M. Santos, Carvalho, Ramos, Dias, & Reis, 2016;Teixeira et al, 2016). Also, some of these studies lack information such as investment in catchment gutters and/or the area where the cistern is located .…”
Section: Resultsmentioning
confidence: 99%
“…Also, some of these studies lack information such as investment in catchment gutters and/or the area where the cistern is located . Moreover, the evaluations were conducted for other economic activities, such as soft drink (M. Santos et al, 2016) and metalworking industries (Teixeira et al, 2016), and homes (Machione & Lopes, 2015;Zocolotti & Haus, 2015). Another point that makes comparison difficult is that the researchers did not consider the land value, which may be underestimating the investment and may lead to a misunderstanding in the expansion advice because although the area looks small, its value is high, especially when the investment is in the urban perimeter, where land is more valued.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ressalta-se que, as tabelas utilizadas para o orçamento se referiram às tabelas de itens de serviço, estando o custo com a mão de obra necessária incluído na composição de cada item.Na quantificação dos custos com as tubulações e conectores necessários, para interligar o novo reservatório aos pontos de alimentação, foi considerado um percentual de 15% do valor do reservatório (LIMA; NUNES; SILVA, 2017; MARINOSKI;GHISI, 2008;FERREIRA, 2007). Para os custos anuais referentes à manutenção do sistema, adotou-se um custo de 20% do valor total da implantação do sistema durante toda a vida útil do sistema, considerando um tempo de vida útil de um sistema de aproveitamento de águas pluviais igual a 20 anos(COSCARELLI, 2010;TEIXEIRA et al, 2016).Para determinar a economia monetária mensal após a implantação do sistema, em R$/mês, calculou-se a diferença entre o Custo médio mensal antes da implantação do sistema e o Custo médio mensal após a implantação do sistema de aproveitamento de água pluvial. Para determinação do Custo médio mensal após a implantação do sistema considerou-se o produto entre o consumo médio mensal da edificação, o potencial de economia gerado pela simulação no programa computacional Netuno e a tarifa de consumo de água cobrada pela concessionária de água, a Companhia Pernambucana de Saneamento -COMPESA, em sua estrutura tarifária para o ano de 2017 (ARPE, 2017), acrescido da taxa de geração de esgoto, equivalente a 100% do valor do consumo de água.…”
unclassified